Edukasi Dismenorea dan Upaya Cara Mengatasinya Pada Remaja di Pondok Pesantren dan Lembaga Kesejahteraan Sosial Anak (LKSA) Bintan Sa’adillah Ar Rosyid - Dwi Yati; Hutasoit, Masta; Jati, Ratih Kumoro (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2024)
Dysmenorrhea is one of the stiffness or constriction in the lower abdomen that occurs in the run up to menstruation or during menstruation. Dismenorrhea has a huge impact on teenage girls because it causes disturbance of day to day activities. Teenage girls who experience menstrual pain (dismenorrhoea) at the time of menstruation will feel limited in doing activities especially in school activities accompanied by dizziness, nausea, vomiting, fever, even to fainting. The purpose of this community service activity is to increase knowledge related to the prevention and treatment of dysmenorrhea. The target of this community service are the teenagers who lives in the Pondok Pesantren dan Lembaga Kesejahteraan Sosial Anak (Lksa) Bintan Sa’adillah Ar Rosyid Bantul, as many as 19 respondents. The community service activity will take place in April 2023. The methods used in this research are lecture methods, visual audio and posters. To measure the level of students' knowledge about dysmenorrhea and its treatment using questionnaires. The results showed that the respondents that before health education most of the knowledge of respondents related to knowledge about prevention and treatment of dysmenorrhea in the sufficient category 57.9%, and after given education experienced an improvement in good category of 57,9%. So it can be concluded that there was an increase in respondents' knowledge after having completed health education.